Β Adrenergic blockers lower renin in patients treated with ACE inhibitors and diuretics. Issue 1 (1st July 1998) - Holmer, S R; Hense, H-W; Danser, A H J; Mayer, B; Riegger, G A J; Schunkert, H
Abstract : Objective: To examine the effect of concomitant intake of β blockers with angiotensin converting enzyme (ACE) inhibitors, diuretics, or both on plasma renin concentrations in a population based sample (MONICA survey, Augsburg, Germany). Subject and methods: 728 individuals were studied, of whom 171 were treated using monotherapy (ACE inhibitor (n = 21), diuretic (n = 10), or β blocker (n = 72)), or combination treatment (ACE inhibitor + diuretic (n = 32), ACE inhibitor + β blocker (n = 7), diuretic + β blocker (n = 22), ACE inhibitor + diuretic + β blocker (n = 7)). The remaining 557 individuals were untreated. Indications for treatment were hypertension (75%), coronary artery disease with (12%) or without (3%) hypertension, or unknown (10%). Results: Mean (SEM) renin concentrations in individuals treated with an ACE inhibitor (41 (8) mU/l), a diuretic (41 (10) mU/l), or the combination of an ACE inhibitor and a diuretic (54 (10) mU/l) were raised compared with untreated individuals (17 (1) mU/l; p < 0.05 each). Monotherapy with a β blocker, however, decreased mean renin concentrations (12 (1) mU/l; p < 0.01 v untreated). Renin concentrations in individuals taking a β blocker with either an ACE inhibitor (21 (8) mU/l), or a diuretic (22 (4) mU/l), or with both an ACE inhibitor and a diuretic (21 (7) mU/L), were significantly lower compared with renin concentrations in groups not receiving β blocker treatment (p < 0.05 each). Conclusion: These data suggest that the upregulation of renin by treatment with ACE inhibitors, diuretics, or both can be largely prevented by concomitant β blocker treatment.